Management of male osteoporosis: report of the UK Consensus Group. - Eastell, R; Boyle, I; Compston, J; Cooper, C; Fogelman, I; Francis, R; Hosking, D; Purdie, D; Ralston, S; Reeve, J; Reid, D; Russell, R; et al. (1998)
Although osteoporosis is generally regarded as a disease of women, up to 30% of hip fractures and 20% of vertebral fractures occur in men. Risk factors for osteoporotic fractures in men include low body mass index, smoking, high alcohol consumption, corticosteroid therapy, physical inactivity, diseases that predispose to low bone mass, and conditions increasing the risk of falls. The key drugs and diseases that definitely produce a decrease in bone mineral density (BMD) and/or an increase in fracture rate in men are long-term corticosteroid use, hypogonadism, alcoholism and transplantation. Age-related bone loss may be a result of declining renal function, vitamin D deficiency, increased parathyroid hormone levels, low serum testosterone levels, low calcium intake and absorption. Osteoporosis can be diagnosed on the basis of radiological assessments of bone mass, or clinically when it becomes symptomatic. Various biochemical markers have been related to bone loss in healthy and osteoporotic men. Their use as diagnostic tools, however, needs further investigation. A practical approach would be to consider a bone density more than one SD below the age-matched mean value (Z < -1) as an indication for therapy. The treatment options for men with osteoporosis include agents to influence bone resorption or formation and specific therapy for any underlying pathological condition. Testosterone treatment increases BMD in hypogonadal men, and is most effective in those whose epiphyses have not closed completely. Bisphosphonates are the treatment of choice in idiopathic osteoporosis, with sodium fluoride and anabolic steroids to be used as alternatives.